Tubeimoside I Inhibits Cell Proliferation and Induces a Partly Disrupted and Cytoprotective Autophagy Through Rapidly Hyperactivation of MEK1/2-ERK1/2 Cascade via Promoting PTP1B in Melanoma - Du, Juan; Dong, Zhen; Tan, Li; Tan, Mengqin; Zhang, Fang; Zhang, Kui; Pan, Guangzhao; Li, Chongyang; Shi, Shaomin; Zhang, Yanli; Liu, Yaling; Cui, Hongjuan (Frontiers in Cell and Developmental Biology, 2020)
Tubeimoside Ⅰ (TBMS1), also referred to as tubeimoside A, is a natural compound extracted from the plant Tu Bei Mu (Bolbostemma paniculatum), which is a traditional Chinese herb used to treat multiple diseases for more than 1000 years. Studies in recent years reported its anti-tumor activity in several cancers. However, whether it is effective in melanoma remains unknown. In the current study, we discovered that TBMS1 treatment inhibited melanoma cell proliferation in vitro and tumorigenecity in vivo. Besides, we also observed that TBMS1 treatment induced a partly-disrupted autophagy, which still remains a protective role, disruption of which by chloroquine (CQ) or 3-methyladenine (3-MA) enhanced TBMS1-induced cell proliferation inhibition. CQ combined with TBMS1 even induced cellular apoptosis. BRAF(V600E) mutation and its continuously activated downstream MEK1/2-ERK1/2 cascade is found in 50 % of melanomas and are important for malanomagenesis. However, hyperactivating MEK1/2-ERK1/2 cascade can also inhibited tumor growth. Intriguingly, we observed that TBMS1 rapidly hyperactivated MEK1/2-ERK1/2, inhibition of which by its inhibitor SL-327 rescued the anti-cancerous effect of TBMS1. Besides, the targets of TBMS1 was predicted by the ZINC Database based on its structure. It is revealed that protein-tyrosine phosphatase 1B (PTP1B) might be one of the targets of TBMS1. Inhibition of PTP1B by its selective inhibitor TCS401 rescued the anti-cancerous effects of TBMS1 in melanoma cells. These result indicated that TBMS1 might activate PTP1B, which further hyperactivates MEK1/2-ERK1/2 cascade, thereby inhibiting cell proliferation in melanoma. Our results provided the potential of TBMS1 as a drug candidate for melanoma therapy and confirmed that rapidly hyperactivating an oncogenic signaling pathway may also be a promising strategy for cancer treatment.